2020
DOI: 10.1371/journal.pone.0230604
|View full text |Cite
|
Sign up to set email alerts
|

Where are patients missed in the tuberculosis diagnostic cascade? A prospective cohort study in Ghana

Abstract: BackgroundGhana's national prevalence survey showed higher than expected tuberculosis (TB) prevalence, indicating that many people with TB are not identified and treated. This study aimed to identify gaps in the TB diagnostic cascade prior to starting treatment. MethodsA prospective cohort study was conducted in urban and rural health facilities in south-east Ghana. Consecutive patients routinely identified as needing a TB test were followed up for two months to find out if sputum was submitted and/or treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…The main health system-related barrier was that the TB diagnostic laboratory was at the municipal hospital which is distant from most rural health facilities, and clients cannot afford the transport cost [ 18 ]. Limited access to diagnostic facilities, mostly in rural settings, and long travel distance were similar barriers experienced by presumed TB clients in other parts of the world [ 6 , 7 , 22 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main health system-related barrier was that the TB diagnostic laboratory was at the municipal hospital which is distant from most rural health facilities, and clients cannot afford the transport cost [ 18 ]. Limited access to diagnostic facilities, mostly in rural settings, and long travel distance were similar barriers experienced by presumed TB clients in other parts of the world [ 6 , 7 , 22 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on an initial assessment of health facilities in April 2018 before the start of data collection, we found that there were no TB case finding activities in the rural health facilities. This made it necessary to introduce the screening tool to HCWs who attended to patients in the consulting rooms of the study rural health facilities to facilitate enrolment for the cohort study [ 18 ] and also as an ethical obligation to help improve TB services. The HCWs were trained by the research team on how to use the screening tool and printed copies of the tool were provided to the rural health facilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access services, so 10 km was established as our screening threshold. 28 In South Africa, women who lived greater than 20 km from a diagnostic hospital were more likely to have advanced disease at time of breast cancer diagnosis, so we established 25 km as our diagnosis threshold. 29 For surgical management, we established 45 km as our distance threshold to keep travel time typically less than 1 hour.…”
Section: Reasonable Travel Distancementioning
confidence: 99%
“…However, this requires multiple steps between sample collection and treatment of a positive case, including a (correctly labelled) sample being sent to the laboratory, testing the sample, producing the result, sending the result back to the referring clinic, informing the patient, and the patient returning for treatment. Pre-treatment loss-to-follow-up (LTFU) in low-income countries is well documented for syphilis and other diseases including tuberculosis [7,8]. One strategy to reduce LTFU is to provide same day results through on-site STI testing.…”
Section: Introductionmentioning
confidence: 99%